Glutathione peroxidase 4 is reversibly induced by HCV to control lipid peroxidation and to increase virion infectivity. Issue 1 (16th December 2014) - Brault, Charlène; Lévy, Pierre; Duponchel, Sarah; Michelet, Maud; Sallé, Aurèlie; Pécheur, Eve-Isabelle; Plissonnier, Marie-Laure; Parent, Romain; Véricel, Evelyne; Ivanov, Alexander V; Demir, Münevver; Steffen, Hans-Michael; et al.
Abstract : Objective: Inflammation and oxidative stress drive disease progression in chronic hepatitis C (CHC) towards hepatocellular carcinoma. HCV is known to increase intracellular levels of reactive oxygen species (ROS), but how it eliminates ROS is less well known. The role of the ROS scavenger glutathione peroxidase 4 (GPx4), induced by HCV, in the viral life cycle was analysed. Design: The study was performed using a replicative in vitro HCV infection model and liver biopsies derived from two different CHC patient cohorts. Results: A screen for HCV-induced peroxide scavengers identified GPx4 as a host factor required for HCV infection. The physiological role of GPx4 is the elimination of lipid peroxides from membranes or lipoproteins. GPx4-silencing reduced the specific infectivity of HCV by up to 10-fold. Loss of infectivity correlated with 70% reduced fusogenic activity of virions in liposome fusion assays. NS5A was identified as the protein that mediates GPx4 induction in a phosphatidylinositol-3-kinase-dependent manner. Levels of GPx4 mRNA were found increased in vitro and in CHC compared with control liver biopsies. Upon successful viral eradication, GPx4 transcript levels returned to baseline in vitro and also in the liver of patients. Conclusions: HCV induces oxidative stress but controls it tightly by inducing ROS scavengers. Among these, GPx4 plays an essential role in the HCV life cycle. Modulating oxidative stress in CHC by specifically targeting GPx4 may lower specific infectivity of virions and prevent hepatocarcinogenesis, especially in patients who remain difficult to be treated in the new era of interferon-free regimens.